Integrated treatment of stormwater using multistage filtration (MSF) for domestic application (reuse) - Chibueze, Chekwubechukwu V; Nnaji, Chidozie C; Mama, Cordelia N; Nwankwo, Ekene J (Water S. A., 2024)
Stormwater harvesting is a promising solution for global freshwater depletion, particularly in tropical regions with abundant rainfall. However, it is not widely used due to the lack of suitable treatment technologies for domestic applications. Multi-stage filtration (MSF) is an efective integrated treatment technology that provides a cost-efective alternative for stormwater treatment. This study investigated MSF's capacity for treating stormwater at diferent stages. The MSF designed and built comprised the down-flow roughing filter (DRF) and slow sand lfiter (SSF). The results achieved by the MSF for the treated efluents were: pH (7.1-8.1), temperature (27.6-29.4°C), electrical conductivity (EC) (100-190 µS/cm) and total dissolved solids (TDS) (70-130 mg/L). Turbidity removal eficiency of the MSF was in the range of 36-99% (5.825-164.05 NTU) and the overall average removal eficiency of the MSF was 74%, 90% and 86% for total coliforms (TC) (360-11 800 CFU/ 100 mL), faecal coliforms (FC) (0-1 300 CFU/100 mL) and Enterococcus spp. (120- 1 400 CFU/100 mL), respectively. The study identified stormwater reuse potentials based on international guidelines and benchmarks. For the treated efluent, pH, temperature, EC and TDS were all within the permissible limits for toilet, laundry, bathing, recreational and agricultural water reuse, while turbidity suited agricultural (non-food crop) and restricted urban reuse. 46% of the efluent was suitable for recreational purposes as this satisfied the 50 NTU standard. 62.5% of the efluent satisfied the FC standard for toilets and urinals and agricultural reuse (non-food crop) purposes, while 87.5 % of the efluent satisfied urban reuse purposes (restricted access). 66.67% of the efluent satisfied the Enterococcus spp. standard for agricultural reuse (non-food crop). All treated efluents satisfied the TC bathing standard. This study shows that after minimal disinfection, stormwater efluents ofer potential reuse in household applications, thereby reducing potable water demand.